Nanocellulose for Military Textiles: Innovations, Applications, and Challenges - Sulfi Indriani; Sri Yanto; I Nengah Putra (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Military textiles must withstand ballistic threats, high temperatures, and chemical exposure while remaining lightweight, durable, and multifunctional. Nanocellulose, especially cellulose nanofibrils (CNF) and cellulose nanocrystals (CNC), offers high specific strength, biodegradability, and tunable surface chemistry, making it a promising complement to conventional high performance fibers such as aramid. This structured review synthesizes peer reviewed studies published from 2015 to 2025 and retrieved from Scopus, Web of Science, and ScienceDirect, focusing on ballistic resistance, flame retardancy, and antibacterial functionality. Evidence shows that CNF and CNC reinforcement improves energy dissipation networks and strength to weight ratios, with several composites approaching aramid based benchmarks. For flame protection, nanocellulose coatings and hybrid layers reduce peak heat release rates by up to 38% and promote dense char barriers that limit heat and mass transfer. Antibacterial performance is typically achieved through functionalization with Ag, ZnO, or chitosan, often delivering over 90% inhibition of Escherichia coli and Staphylococcus aureus. Key barriers include production cost and scalability, moisture sensitivity that can reduce long term durability, and weak interfacial compatibility with aramid and ultra high molecular weight polyethylene (UHMWPE). Future work should prioritize scalable green manufacturing, interface engineering for durable hybrids, and validation under military relevant durability and laundering standards. Overall, nanocellulose is a strong candidate for next generation sustainable military textiles.